Unpacking Province Creation in The Philippines - Michael Tumanut (Scientia)
To enhance service delivery and local democracy, legislators have tinkered with size or status of local governments in the Philippines. This elasticity in local borders has been more evident at the province level, the highest local government tier. Since 1987, a new province is birthed roughly every three years. As the determinants and mechanisms of contemporary province fragmentation are under-examined, this article investigates, at several policymaking levels and dimensions, attempts to redraw borders of Philippine provinces. Framed by an institutional framework and a case-study approach, and employing a veto-player analysis, heuristic cases of two provinces (Quezon and Zamboanga del Sur) were unpacked and compared. Findings reveal that there is a large and fragmented veto-player group in the area of territorial rescaling of provinces. Congruence of preferences among veto players was observed to be influenced by territorial leveraging, pivot on networks and reciprocity norm, and mirroring of preferences. The tenacity and strategic actions of reform agent or policy entrepreneur (usually the congressman), sometimes assisted by social movement, is likewise found crucial in the pathways leading to reform outcomes. In a simple cross-case analysis of recent reform attempts, findings also suggest that the provinces’ core-periphery location pattern, and proposed type of spatio-jurisdictional partition are associated with reform outcomes.